Mechanism of development of coal dust continuous explosion in a network of mine workings (Rudarsko-geološko-naftni zbornik, 2022)
The objective of the paper is to reveal the mechanism of creating conditions for continuous explosion of coal dust by transferring seismic energy to coal dust located along the perimeter of a working. The ANSYS software package was used to model of the movement of coal dust particles in the air under the influence of seismic waves caused by the action of an explosion. It was confirmed by modelling that seismic waves, provoked by the explosion, propagate in the rock mass at a higher velocity than the moving explosive front in the air of a working. Qualitative and quantitative behaviour of a layer of coal dust in the process of oscillation of the working walls under the influence of seismic waves during one second was described. The stage of dynamic loosening of the powder is supplemented by the initial period of the mechanism of explosion development, when there are no combustible concentrations of gas or coal traces in the air composition of the mine working before the accident. It is established that under the seismic influence at a distance of about 50 m from the hypocentre of the explosion, a layer of powder-like dispersed coal rises into the air forming a dust cloud, which is the initiator of further continuous development of the explosion spreading in a network of mine workings.